1996
DOI: 10.3354/meps140123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical and chemical factors on settlement and recruitment of the hydroid Tubularia larynx

Abstract: ABSTRACT. Field observations using settlement panels, which were carried out in Port Daniel Bay, Baie des Chaleurs, Quebec, Canada, in 1992, showed recruitment by the hydi-oid Tubularla laj-ynx to be unevenly distnbuted with depth Multiple regression on residuals indicated that 2 physlcal factors, water temperature and light intensity, out of 5 tested explained 45%) of the observed variance in the recruitment of T. larynx on the panels In laboratory experiments, warm temperatures increased settlement significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Only preliminary studies have been carried out on the behavior and settlement process of the actinula larva (Pyefinch and Downing, 1949;Berrill, 1952;Hawes, 1958;Orlov and Marfenin. 1994), and a few ecological studies on larval recruitment have been performed (Lemire and Bourget, 1996;Nellis and Bourget, 1996;Walters and Wethey, 1996). Berrill (1952) and Hawes (1958) suggested that the temporary attachment of the actinula was achieved by nematocyst discharge from the aboral tentacle tips.…”
Section: Introductionmentioning
confidence: 99%
“…Only preliminary studies have been carried out on the behavior and settlement process of the actinula larva (Pyefinch and Downing, 1949;Berrill, 1952;Hawes, 1958;Orlov and Marfenin. 1994), and a few ecological studies on larval recruitment have been performed (Lemire and Bourget, 1996;Nellis and Bourget, 1996;Walters and Wethey, 1996). Berrill (1952) and Hawes (1958) suggested that the temporary attachment of the actinula was achieved by nematocyst discharge from the aboral tentacle tips.…”
Section: Introductionmentioning
confidence: 99%
“…After release, larvae are non-feeding and swim for a few hours (Woollacott & Zimmer 1971). In still water, when the swimming phase is complete, larvae become photonegative and geopositive and begin to explore surfaces (Lynch 1947, Nellis & Bourget 1996. Individuals swim in counter-clockwise circles of decreasing circumference over the surface, 'testing' the substrate with bundles of cilia (Woollacott & Zimmer 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The observed increase in colonies during spring could be the result of re‐growth, self recruitment or settlement of recruits from northern sources. Moreover, actinulae settlement is known to be enhanced by higher temperatures (Nellis & Bourget ).…”
Section: Discussionmentioning
confidence: 99%